Transparency in the Management of Thai Women Empowerment Fund: Case Study of the Occupation Groups, Sawankhalok District, Sukhothai Province - Khongsatjaviwat, Darin (Journal of Social Sciences Naresuan University, 2026)
This research article aimed to examine transparency in the operations of the Thai Women Empowerment Fund, using an occupational group in Wang Phinphat Subdistrict, Sawankhalok District, Sukhothai Province, as a case study. It also proposes guidelines for strengthening good governance in fund management. The study employed qualitative research methods, collecting data through documentary research and semi-structured, in-depth interviews with 10 key informants. Data were analyzed using content analysis based on the six principles of good governance established by the Office of the Civil Service Commission, including the rule of law, virtues, transparency, accountability, effectiveness, and participation. The findings revealed that the fund demonstrated a high level of transparency and community-based transparency through mechanisms such as financial information disclosure, clarification meetings, and external monitoring by government agencies, which helped strengthen members’ confidence in the fund administration. However, the major problems included the lack of a strong internal auditing system and excessive reliance on community-based relationships. Therefore, the study suggests that the governance system should be improved through amended regulations, the establishment of monitoring mechanisms, and systematic public disclosure of information to enhance transparency and ensure sustainable management of the fund.